Effects of topical and subconjunctival use of bevacizumab on corneal neovascularization in rabbits' eyes - Lopes,Gerson Jorge Aparecido (2017)
ABSTRACT Purpose: To evaluate and compare the effects of topical application and subconjunctival injection of bevacizumab on corneal neovascularization (CNV) in rabbits' eyes after chemical burning of the cornea. Methods: The animals were randomly distributed into four groups of five animals. In one group, the drug was instilled, while in another, it was administered by subconjunctival injection. The two procedures using bevacizumab were compared with instillation and subconjunctival injection of saline solution (S). Neovascularization was evaluated according to the size of the invasion area of new blood vessels and through computerized analysis of this area. The data were analyzed using the Kruskal-Wallis test followed by Dunn's test for two-by-two comparison of the groups, to assess the external examination of CNV. Analysis of variance was used to assess the area of CNV. P<0.05 was considered statistically significant. Results: Assessing both the external examination and the invasion area of neovessels on the 5th and 10th days, there was a clear difference between the groups. The group to which saline solution had been applied showed higher scores for CNV, as well as increases in the invasion area of neovessels. Two-by-two comparison of groups revealed no significant differences. However, an analysis of the factors involved (injection vs. instillation and bevacizumab vs. saline solution) showed that injection did not differ from instillation, but that bevacizumab differed from saline solution. Conclusion: Bevacizumab showed an inhibitory effect on CNV in rabbits' eyes after chemical burning of the cornea. There was no difference between the topical or subconjunctival administration of bevacizumab in the inhibition of CNV.